2021
DOI: 10.3389/fpsyg.2021.679001
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward and Susceptibility to Doping in Spanish Elite and National-Standard Track and Field Athletes: An Examination of the Sport Drug Control Model

Abstract: The Sport Drug Control Model (SDCM) is likely to be the model which most explicitly represents the theoretical paradigm of the psychological study of the use of doping in sport. This model can be further developed through its analysis in different populations and cultures. The main aim of this study was to empirically test the SDCM while analyzing for the first time the intentions and attitudes toward doping in Spanish track and field athletes. A secondary aim was to assess the extent to which the variables in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 46 publications
3
14
2
4
Order By: Relevance
“…A larger sample of athletes, especially involving those in a wider variety of sports branches, would allow one to examine the extent to which the interrelationships between moral identities, perception of fair play, and doping attitudes occur depending on the sport. This claim corresponds with recent research that attempted to analyze attitudes and views on doping in particular sports such as track and field [ 57 ] or, more specifically, elite distance running [ 58 ]. Such analyses are also encouraged by doping control test findings showing that detected banned substances in anti-doping control tests differ depending on the sports discipline [ 5 ].…”
Section: Discussionsupporting
confidence: 79%
“…A larger sample of athletes, especially involving those in a wider variety of sports branches, would allow one to examine the extent to which the interrelationships between moral identities, perception of fair play, and doping attitudes occur depending on the sport. This claim corresponds with recent research that attempted to analyze attitudes and views on doping in particular sports such as track and field [ 57 ] or, more specifically, elite distance running [ 58 ]. Such analyses are also encouraged by doping control test findings showing that detected banned substances in anti-doping control tests differ depending on the sports discipline [ 5 ].…”
Section: Discussionsupporting
confidence: 79%
“…The study by Mazzeo and colleagues [16] revealed that use of doping substances would result in less social phobia in athletes. Another study by García et al [17] showed that attitudes, normative beliefs, situational temptation, and behavioral control significantly predicted doping intentions that all these were as a social cognition.…”
Section: Figure 1-frequency Of Social Phobia In Both Groupsmentioning
confidence: 97%
“…Coaches strongly influence athletes' attitudes toward doping and can shape athlete's beliefs, behaviors, and decisions to be for or against doping (Barkoukis et al, 2019 ; García-Grimau et al, 2021 ). The impact of the athlete's entourage on attitudes toward doping has been reported in different studies (Backhouse and McKenna, 2012 ; Mazanov et al, 2014 ; Engelberg and Moston, 2016 ) and the coach is considered part of the Athlete Support Personnel (ASP) as well as parents/guardians, physiotherapists and other professionals supporting and working directly with athletes, as defined by the World Anti-Doping Code (WADC) (World Anti-Doping Agency, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…Findings from a cluster randomized controlled trial reported that coaches adopting a motivational climate reduced athlete willingness to dope (Ntoumanis et al, 2021 ). In addition, moral disengagement was strongly correlated with doping attitudes and intentions toward doping in athletes (Kavussanu et al, 2019 ; García-Grimau et al, 2021 ) and plays an important role in coaching style and climate (Hodge and Lonsdale, 2011 ; Chen et al, 2017 ). Moreover, recent qualitative evidence (Patterson and Backhouse, 2018 ; Barkoukis et al, 2019 ) reported that displacement and diffusion of responsibility, which are considered two of the mechanisms involved in the moral disengagement construct (Bandura et al, 1996 ), influence coaches' opinions and behavior toward doping.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation